The new universe and the human future how a shared cosmology could transform the world - Abrams, Nancy Ellen, 1948-; Primack, J. R. (Joel R.); ebrary, Inc. (New Haven [Conn.] : Yale University Press, 2011)
"After a four-century rupture between science and the questions of value and meaning, this groundbreaking book presents an explosive and potentially life-altering idea: if the world could agree on a shared creation story based on modern cosmology and biology--a story that has just become available--it would redefine our relationship with Planet Earth and benefit all of humanity, now and into the distant future. Written in eloquent, accessible prose and illustrated in magnificent color throughout, including images from innovative simulations of the evolving universe, this book brings the new scientific picture of the universe to life. It interprets what our human place in the cosmos may mean for us and our descendants. It offers unique insights into the potential use of this newfound knowledge to find solutions to seemingly intractable global problems such as climate change and unsustainable growth. And it explains why we need to "think cosmically, act globally" if we're going to have a long-term, prosperous future on Earth"--
"Most people assume either that Earth was created as-is a few thousand years ago, or else that it's a lonely rock in endless space--although both assumptions are wrong. Meanwhile, global problems like climate destabilization, economic chaos, religious-justified violence, and exhaustion of planetary resources are escalating. These facts are connected. The new universe picture described in this book provides a believable new origin story and cosmic context, which help us to think for the first time on large enough time and size scales to see how to keep Earth and the human species healthy long into the future"--
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Cosmology -- Philosophy; Life -- Origin -- Philosophy; Electronic books